Does ESG Disclosure and Audit Quality Influence The Bank’s Financial Performance? - Nisriinaa Yumnaa 'Aatikah; Siti Mutmainah (International Journal of Economics Development Research (IJEDR), 2024)
Bank play an important role in the global economy makes the sustainability report disclosure and audit quality of banks becoming more important for stakeholders to make decisions. This study was conducted to find out whether ESG disclosure and audit quality affect bank performance. In this study, ESG disclosure variables were obtained from the Bloomberg database, audit quality was measured using dummy variable proxies, bank performance variables were measured using ROA and ROE. This study uses a sample of banks listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. The analysis technique involves multiple linear regression analysis using SPSS 26 software. The results show that ESG disclosure are not significantly related to ROA but has a significant positive effect on ROE and audit quality has a significant negative effect on ROA but not significantly related to ROE.